Kontribusi Ulama Sufi dalam Keutuhan NKRI - Irsad Akil, Irsad (Mahad Aly Al Fithrah, 2021)
In the historical record, many religious figures played a role in Indonesia's independence but there are also not recorded in the dictionary of national heroes, such as the role of Sufi scholars who have contributed in fighting for and defending sovereignty in Indonesia, it is with their unique and unreasonable attack strategies. The article aims to re-research contributions of Islamic scholars in maintaining the integrity of Indonesia, especially among Sufis. This research is library and uses history-philosophy in his analysis. The result in this article is that was recorded in 1825 to 1830 the occurrence of resistance by the character of the order, Prince Diponogoro with the support of scholars Sufism in the resistance with Dutch Colonials. In addition, there are movements and resolutions carried out by a scholar named K.H Hashim Asy'ari, until inflame spirit of resistance santri. Then, the movement disciples of Sheikh Ahmad Khatib who was the founder of the Qodiriyyah Naqsandiyyah order gave their action about resistance in Cilegon near Batavia. This action actually gave losses to the Dutch colonial.